2018
DOI: 10.7196/samj.2017.v108i2.12524
|View full text |Cite
|
Sign up to set email alerts
|

The development of hospital-based palliative care services in public hospitals in the Western Cape, South Africa

Abstract: Author contributions. RK, LG and PR conceived the article. LG wrote the introduction and development sections. RK, PR and TC composed the section on GSH.LG, HG and JS were responsible for the partnership section.RK, LG, PR and CC wrote on identifying patients. LG and RK compiled the community resources section. All co-authors reviewed the article, added comments and made editorial changes, which were included by LG.Funding. None. Conflicts of interest.None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 10 publications
(11 reference statements)
0
35
0
Order By: Relevance
“…This was facilitated using referrals and members from the PC team attending ward rounds or offering consultations on symptom management. ‘Outpatient clinics’: many interventions used this mechanism to integrate PC into a facility, ( Molyneux et al , 2013 ; DesRosiers et al , 2014 ; Cornetta et al , 2015 ; Lowther et al , 2015 ; Zipporah, 2016 ; Gwyther et al , 2018 ). Usually individuals were seen together with their caregiver; however group outpatient clinics were also described ( DesRosiers et al , 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was facilitated using referrals and members from the PC team attending ward rounds or offering consultations on symptom management. ‘Outpatient clinics’: many interventions used this mechanism to integrate PC into a facility, ( Molyneux et al , 2013 ; DesRosiers et al , 2014 ; Cornetta et al , 2015 ; Lowther et al , 2015 ; Zipporah, 2016 ; Gwyther et al , 2018 ). Usually individuals were seen together with their caregiver; however group outpatient clinics were also described ( DesRosiers et al , 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…These were often home visits ( Herce et al , 2014 ), according to set criteria, such as those whose mobility is heavily effected ( Hongoro and Dinat, 2011 ) and children whose caregivers could not carry them in ( Amery et al , 2009 ), and also found in the form of mobile clinics ( Herce et al , 2014 ), visits to other facilities, such as children homes ( Amery et al , 2009 ) and other health centres ( Tapsfield and Bates, 2011 ). ‘Telephonic advisory service’: telephonic consultations were used to manage patients’ symptoms at home ( Hongoro and Dinat, 2011 ; Cornetta et al , 2015 ) and to provide follow-up and bereavement calls ( Gwyther et al , 2018 ). ‘Treatment plans’: specialist PC teams often developed care plans that would be used while the patient is in the facility and following discharge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A simplified version (in particular designed to fit on a single printed page) of the GSF-PIG has been used in two public sector hospitals in the Western Cape Province for several years already to aid clinicians in the identification and referral of patients for local palliative care programs. 18 This study aims to test the shortened GSF-PIG tool in patients admitted to general medical wards in two public sector hospital in South Africa, in the context of the double burden of disease. 19…”
Section: Such Tools Have Not Been Formally Tested In South Africa (Samentioning
confidence: 99%
“…The South African National Policy on Palliative care of 2017 suggested development of a SA Palliative Care assessment tool modelled on the GSF-PIG and SPICT, but also discusses that this tool still needs to be validated for general use [1]. A simplified version (in particular designed to fit on a single printed page) of the GSF-PIG has been used in two public sector hospitals in the Western Cape Province for several years already to aid clinicians in the identification and referral of patients for local palliative care programs [18].…”
Section: Introductionmentioning
confidence: 99%